Critical & analytical thinking - Prasad, A.S.; Agarwal, Shailja (Delhi: Cengage Learning India Pvt. Ltd., 2024)
Identifies the textbook titled Critical and Analytical Thinking. This comprehensive guide is designed as an essential reference for students and professionals looking to enhance their reasoning and decision-making skills.
Keywords: Problem solving; Logic Development; Decision Making; Managerial Communication